Absence of detrusor muscle in TUR-BT specimen – can we predict who is at highest risk? - Yannic Volz; Rabea Trappmann; Benedikt Ebner; Lennert Eismann; Nikolaos Pyrgidis; Paulo Pfitzinger; Robert Bischoff; Boris Schlenker; Christian Stief; Gerald Bastian Schulz (BMC Urology, 2023)
Abstract Introduction As a high-quality TUR-BT is important to ensure adequate treatment for bladder cancer patients, the aim of the current study is to investigate the impact of patient-related, surgical and tumor-specific parameters on detrusor muscle (DM) absence (primary objective) and to assess the impact of DM on the prognosis after a TUR-BT (secondary objective). Patients and methods Transurethral resection of bladder tumors (TUR-BTs) between 2009 and 2021 were retrospectively screened (n = 3237). We included 2058 cases (1472 patients) for the primary and 472 patients for secondary objective. Clinicopathological variables including tumor size, localization, multifocality, configuration, operation time and skill-level of the urologist were assessed. We analyzed predictors for missing DM and prognostic factors for recurrence-free survival (RFS) for the complete cohort and subgroups. Results DM was present in 67.6% (n = 1371/2058). Surgery duration (continuous, minutes) was an independent predictor for absence of DM in the complete cohort (OR:0.98, r:0.012, 95%CI:0.98–0.99, p = 0.001). Other significant risk factors for missing DM were papillary tumors (OR:1.99, r:0.251, 95%CI:1.22–3.27, p = 0.006) in the complete cohort and bladder-roof and posterior-bladder-wall localization for re-resections. Absence of DM in high-grade BC correlated with reduced RFS (HR:1.96, 95%CI:1.0–3.79, p = 0.045). Conclusion Sufficient time for a TUR-BT is mandatory to assure DM in the TUR-BT specimen. Also, cases with more difficult locations of bladder tumors should be performed with utmost surgical diligence and endourological training should incorporate how to perform such operations. Of note, DM correlates with improved oncological prognosis in high-grade BC.